Real Analyticity of Hausdorff Dimension Function of Disconnected Julia Sets of Parabolic Polynomials fa,b(z) = z(1 – az – bz2) - Akter, Hasina (GANIT: Journal of Bangladesh Mathematical Society, 2018)
Abstract not available GANIT J. Bangladesh Math. Soc.Vol. 38 (2018) 119-125